2009
DOI: 10.1063/1.3153157
|View full text |Cite
|
Sign up to set email alerts
|

Temperature stability of ([Na0.5K0.5NbO3]0.93–[LiTaO3]0.07) lead-free piezoelectric ceramics

Abstract: A polymorphic phase transition (PPT) is often engineered into lead-free materials to generate high piezoelectric activity at room temperature, limiting their temperature stability. We report [Na0.5K0.5NbO3]0.93–[LiTaO3]0.07 tetragonal ceramics with favorable properties over a broad temperature range due to a high Curie temperature at 447 °C and PPT at −15 °C involving a transition to a monoclinic rather than low temperature orthorhombic phase. Piezoelectric k31 and d31 coefficients varied from 0.19 to 0.14 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 15 publications
0
48
0
Order By: Relevance
“…The M phase was assumed to have an orthorhombic symmetry from previous studies on the x¼1 compound KNbO 3 (KN) [5][6][7]. However, although Li-doped NKN has been reported to have a monoclinic symmetry [8,9], no structural data for pure NKN is available to date in the inorganic crystal structure database [10].…”
Section: Introductionmentioning
confidence: 99%
“…The M phase was assumed to have an orthorhombic symmetry from previous studies on the x¼1 compound KNbO 3 (KN) [5][6][7]. However, although Li-doped NKN has been reported to have a monoclinic symmetry [8,9], no structural data for pure NKN is available to date in the inorganic crystal structure database [10].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the (Li, Ta, Sb)-modified NKN ceramics were reported to have comparable piezoelectric properties to those of some commercial PZT ceramics [5][6][7][8]. The piezoelectric and electromechanical properties have been so far obviously modified through a lot of attempts to optimize the composition and processing [7][8][9], and to improve the thermal stability [4,9]. It can be found that most of these researches were focused on conventional solid-state reaction methods for making random NKN based piezoelectric ceramics.…”
Section: Introductionmentioning
confidence: 96%
“…The hot-pressing technique as well as spark plasma sintering (SPS) with high densities produce materials with excellent piezoelectric properties [15], but such processing techniques are not appropriate for industrial applications. The incorporation of LiTaO 3 into the perovskite structure of NKN improves piezoelectric properties [16,17]. The best piezoelectric properties of the (1 − x)K 0.5 Na 0.5 NbO 3 -xLiTaO 3 ((1 − x)NKN-xLT) system have been achieved at the MPB region where x = 5-6 mol%.…”
Section: Introductionmentioning
confidence: 97%